Effects of soil composition and curing conditions on the strength and durability of Cr3+-crosslinked biopolymer-soil composites - Bang, Jeong Uk; Lee, Minhyeong; Park, Dong Yeup; Chang, Ilhan; Cho, Gye Chun (Construction and Building Materials, 2024)
Stabilized soil composites incorporating Cr3+-crosslinked xanthan gum (CrXG), a self-stiffening cation-crosslinked biopolymer, have recently emerged as sustainable construction materials for earthen structures. However, the influence of curing conditions and soil composition in altering the mechanical properties of CrXG–soil composites has so far received limited attention. This study investigates the effects of fine contents and curing conditions on the time-dependent strength development and durability of CrXG-soil composites. CrXG-soil composites, ranging from poorly graded sand to clayey silty sand, are subjected to unconfined compressive strength (UCS) and durability tests under various curing conditions, including wet, submerged, and dry conditions. Microscopic structural changes are characterized using scanning electron microscopy (SEM) and Fourier-transform infrared spectroscopy (FTIR). The results showed that the UCS of CrXG-soil composite increases nonlinearly, reaching up to 4.8 times the initial wet UCS after 28 days of curing, closely aligning with predictions from a hyperbolic model. Notably, CrXG-soil compositions with a clay-sand mixture (CSM) containing 15 % fine content (CSM15) demonstrated consistent strength parameters across all curing conditions in UCS tests. CSM15 also maintains a 90 % of durability index after eight dry-wet cycles and a dry UCS of 300 kPa after 130 days of atmospheric weathering. Microscopic-scale analysis confirms the stable agglomeration of CrXG-clay matrices between sand grains, with the peak wavelength of the major functional group remaining constant, even under multiple cycles. These findings contribute to a deeper understanding of CrXG–soil composites, offering valuable insights into optimizing soil compositions and enhancing the technical feasibility of applying these composites as a sustainable surface protection strategy for earthen structures, such as levees and road slopes.
Keywords: Biopolymer–soil composite; Clay/sand mixtures; Crosslinked; Curing condition; Fines content; Sand-fine mixture; Soil composition; Soil stabilization; Strength; Unconfined compressive strength; Biopolymer–soil composite; Durability; Fine content; Sand-fine mixture; Soil stabilization; Strength